2015
DOI: 10.1007/s10995-015-1683-4
|View full text |Cite
|
Sign up to set email alerts
|

Age at Autism Spectrum Disorder (ASD) Diagnosis by Race, Ethnicity, and Primary Household Language Among Children with Special Health Care Needs, United States, 2009–2010

Abstract: We examined prevalence of diagnosed autism spectrum disorder (ASD) and age at diagnosis according to child’s race/ethnicity and primary household language. From the 2009–2010 National Survey of Children with Special Health Care Needs, we identified 2729 3–17-year-old US children whose parent reported a current ASD diagnosis. We compared ASD prevalence, mean diagnosis age, and percentage with later diagnoses (≥5 years) across racial/ethnic/primary household language groups: non-Hispanic-white, any language (NHW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
57
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(68 citation statements)
references
References 36 publications
(50 reference statements)
5
57
0
4
Order By: Relevance
“…However, it should be noted that there were no significant differences between White and Black parents in education, although White participants were significantly more likely to be recruited from the clinical than the research sample. Furthermore, at least one prior study that reported underdiagnosis of Black children without ID found no relationship between diagnosis rates and parental education (Jo et al 2015). …”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…However, it should be noted that there were no significant differences between White and Black parents in education, although White participants were significantly more likely to be recruited from the clinical than the research sample. Furthermore, at least one prior study that reported underdiagnosis of Black children without ID found no relationship between diagnosis rates and parental education (Jo et al 2015). …”
Section: Discussionmentioning
confidence: 97%
“…Prior studies have reported that Black children are under-represented in ASD diagnosis rates, with Black youth without intellectual disabilities at even greater risk of being under-diagnosed and misdiagnosed (Jo et al 2015), as their impairments may be less obvious or may be conceptualized as behavioral problems. Reduced access to specialty mental health services, clinician bias, and other factors may lead to more impaired Black children with ASD without intellectual disability receiving alternate diagnoses (e.g., conduct disorder, ADHD) and/or never being referred to ASD specialist services.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Canadian born children are most commonly diagnosed between the ages of 39 and 55 months, depending on the region in Canada where these children reside (Ouellette-Kuntz et al 2009). The trend is particularly striking in the United States for autism diagnoses of mild/moderate levels of severity diagnosed who are more likely to be identified at significantly later ages for minority groups (Heejoo et al 2015). This delay in diagnosis has been attributed to a number of clinical, socio-demographic and geographic factors (Daniels and Mandell 2013).…”
Section: Migration and Access To Servicesmentioning
confidence: 99%
“…Given that adaptive behavior scales are standardized by age, the latter finding may suggest failure to make age‐expected gains in this population as a whole. The finding that IQ and verbal ability explained more variance than race is interesting in light of prior work finding that Black children with ASD were more likely to have a comorbid diagnosis of an intellectual disability [Baio et al, ], and questions regarding whether this suggests the potential of missing mild or moderate cases of ASD in Black youths [Jo et al, ].…”
Section: Discussionmentioning
confidence: 98%